(untitled) (mathematica didactica, 2002)
Based on an analysis of relevant high-profile psychological studies the „Pop- Up-Ikonogramm“ has been developed as a concept for a multi-media format of specific mathematical content. This concept was tested empirically in reference to its effectiveness for learning of mathematical propositions and proofs. Compared to the classical versions of media formats the „Pop-Up-Ikonogramm“ proves to be significantly superior in regard to the mathematical reproduction efficiency.